Modern principles of orthodontic treatment of distal occlusion with impaired respiratory function in the period of variable bite (literature review) - Lykhota, К. М.; Vataga, К. А. (Actual Dentistry, 2024)
Introduction. In recent years, there has been a significant increase in the number of scientific publications and interest in the correlation between orthodontic treatment and respiratory function. Most studies of the effects of orthodontic appliances on the airway in the past have been limited by the technological limitations of cephalometric imaging, meaning that reliable analysis of mediolateral airway width has not been possible. Of great interest is the study of the effect of fixed and removable functional devices in the treatment of distal occlusion and impaired respiratory function in the period of variable bite. Purpose: based on the analysis of literary sources, to determine the effect of functional orthodontic equipment on the effectiveness of treatment of distal occlusion and normalization of respiratory function in the period of variable bite. Materials and methods.Information search and analysis of scientific sources was carried out using scientometric databases Web of Science, PubMed, Google Scholar over the past 15 years. Conclusion. The results of numerous scientific studies presented in the review confirm the positive impact of functional orthodontic equipment on the effectiveness of treatment of distal occlusion and normalization of respiratory function during the variable bite period and the need for a multidisciplinary approach to their complex treatment.